Thin Films of Amorphous Molecular Semiconductors for Generating Surface Templates of Regulated Structures - M.Yu. Barabash; V.E. Martynchuk; R.V. Litvin (Журнал нано- та електронної фізики)
In this paper we propose a new approach to the formation of the electret templates by electrophotographic process and perform the 1 cm2 template with a period of ~ 2 microns formed by electrophotographic method of nanocomposite photoconductor film exposure by hologram. A methodic for obtaining of two-dimensional periodic metal-dielectric structures by template method of hologram light field exposure with a period of 0.8-6 mm and a relief height 3.5-650 nm is developed. The possibility of extremely wide range of organic and inorganic compounds in a vacuum, with gas and liquid phases deposition on the surface of the described electret template is shown.